New Records of Euglenophyceae for Turkish Freshwater Algae - Varol, Memet; Sen, Bulent (Central Fisheries Research Inst, 2016)
Phytoplankton samples were collected from four different water bodies in the Tigris River basin in 2008. Nine Euglenophyceae taxa at specific and infraspecific level are reported for the first time on Turkish freshwater algal flora. New records come from six sampling sites in the study area. These taxa consist of one Euglena Ehrenberg (E. sociabilis), two Strombomonas Deflandre (S. planctonica and S. pascheriana), four Trachelomonas Ehrenberg (T. nigra, T. aspera, T. borodiniana and T. scabra var. labiata) and two Phacus Dujardin (P. inflexus and P. ovalis). Identification keys and general information on the morphology and taxonomy of the species are briefly described in this paper, with original illustrations.
Türkiye tatlısu algleri için yeni euglenophyceae kayıtları
Keywords: Euglenophyceae; new records; freshwater algal flora; Tigris River basin; Turkey